1981
DOI: 10.1016/0309-1651(81)90160-0
|View full text |Cite
|
Sign up to set email alerts
|

Blue light as a medium to influence oscillatory contraction frequency in physarum

Abstract: Blue light (496 nm; threshold intensity approximately 1500 Lux) induces a transient frequency decrease of oscillatory contraction automaticity in Physarum. Many, but not all specimens react by an increase in the force amplitude of longitudinal contraction. The spectral region of 496 nm provokes a photophobic response of the plasmodia. The blue light reaction of radial and longitudinal contraction activities decreases with increasing distance from the irradiated area. The light-induced decrease in frequency can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…[17,40,41], and Physarum polycephalum [4,15,22]. Since our interlink feedback scheme uses separate culture dishes, we can realize artificial interaction among various target microbes inhabiting different environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17,40,41], and Physarum polycephalum [4,15,22]. Since our interlink feedback scheme uses separate culture dishes, we can realize artificial interaction among various target microbes inhabiting different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows the temporal evolution of the TMs in two pairs of opposite spokes (indexed as 1 and 9, or 2 and 10, clockwise from the top), obtained in the digital feedback experiments executed under rule combinations (1, 2), (2,3), and (1,4). The imposed rule combination (2, 3) is simultaneously satisfied by only two out of all possible patterns (12870 2 ), whereas the combination (1, 4) cannot be satisfied by any patterns.…”
Section: Pattern Operation With Digital Interlink Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneer articles on photomovement of Physarum reported that plasmodium exhibits the most pronounced negative phototaxis to blue and white light [20,54]. The illumination increase causes changes in the plasmodiumʼs oscillatory activity; the degree of change is inversely proportional to the distance from the light source [71,21]. The exact mechanism of the response to light is as yet unknown.…”
Section: Optical Sensorsmentioning
confidence: 97%
“…Being light sensitive [71,21,2], Physarum could play the role of a primitive eyelike organ. To test this possibility we undertook a series of experiments, one of which is described below.…”
Section: Growth Of Information Pathwaysmentioning
confidence: 99%